Penerapan Action RPG pada Perangkat Mobile Berbasiskan iOS - Yulianto, Budi; Kharisma, Panji; Mirhard, Eko (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Mobile games develop along with technological developments. Gaming applications by applying special graphics technologies optimizes any mobile device. The purpose of this study is to design an Action RPG game application by applying Cocos2d technology to be implemented on mobile devices based on IOS operating system. This study performs data collecting and analyzing, interface designing, application implementation, and application evaluation using the Waterfall Model. Data collection is withdrawn from several surveys related to user needs and similar games. Progressing the study, gameplay design is performed using UML, the data storage structure, and interface design. The study results in an Action RPG game application that is implemented on mobile devices. The results showes that Action RPG games can be developed by incorporating elements of art, graphics, and stories that enhance user's interests.